(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the educational and philosophical lexicon of the Old Uzbek language from linguo-cognitive and linguo-cultural perspectives. Based on historical texts and linguistic analysis, it examines the formation, semantic evolution, and cultural significance of key lexical units. Special attention is given to the challenges faced in identifying modern equivalents, terminological inconsistencies, and the interpretation of polysemous terms. The findings are relevant for scholars in linguistics, historical semantics, philosophy of language, and cultural studies.